2021
DOI: 10.1007/s00423-021-02154-4
|View full text |Cite|
|
Sign up to set email alerts
|

A tailored approach in lymph node-positive perihilar cholangiocarcinoma

Abstract: Purpose Extended right hepatectomy is associated with wide surgical margins in PHC and often favored for oncological considerations. However, it remains uncertain whether established surgical principles also apply to the subgroup of node-positive patients. The aim of the present study was to define a tailored surgical approach for patients with perihilar cholangiocarcinoma (PHC) and lymph node metastases. Methods We reviewed the course of all consecutive p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 26 publications
0
27
0
Order By: Relevance
“…Previous studies reported comparable differences between the survival rates for patients with and without lymph node involvement [4,6,19]. For patients with locally advanced disease who do not undergo resection, median OS rates of 12 months are reported.…”
Section: Discussionmentioning
confidence: 81%
“…Previous studies reported comparable differences between the survival rates for patients with and without lymph node involvement [4,6,19]. For patients with locally advanced disease who do not undergo resection, median OS rates of 12 months are reported.…”
Section: Discussionmentioning
confidence: 81%
“…Although R0 status was part of the TO definition in half of the TO studies [13,17,19,20], we decided not to include it in the definition of TO in PHC surgery for several reasons. First, the perihilar region is narrow and R1 resection is not uncommon in PHC surgery [28][29][30] and patients benefit from surgical resection even in case R1 status is obtained. Second, especially in the subset of lymph nodepositive patients which counts up to almost 50%, survival is independent of R status [30].…”
Section: Discussionmentioning
confidence: 99%
“…First, the perihilar region is narrow and R1 resection is not uncommon in PHC surgery [28][29][30] and patients benefit from surgical resection even in case R1 status is obtained. Second, especially in the subset of lymph nodepositive patients which counts up to almost 50%, survival is independent of R status [30]. Third, PHC surgery is characterized by high perioperative morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Nineteen studies comprising a total of 5595 patients who received one of the following four different treatments after radical resection—ACT, ART, ACRT and surgical resection alone (observation group)—were included in our analysis. It is worth noting that 34 studies11 41–73 were excluded because of unbalanced or unclear baselines. Of the included patients, 2774 patients received adjuvant treatments following curative-intent resection, and 2821 patients underwent curative-intent resection without adjuvant treatments.…”
Section: Resultsmentioning
confidence: 99%